Pengaruh Faktor Makroekonomi dan Penurunan Tarif Pajak Penghasilan Badan Terhadap Produk Domestik Bruto Perkapita Indonesia - Rinaldi Rustam; Zikra Masegus; Mona Adriana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the impact of macroeconomic factors and the reduction in corporate income tax rates on Indonesia's economic growth 2017-2022. The data used is quarterly data from the first quarter of 2017 to the fourth quarter of 2022 from Bank Indonesia and Badan Pusat Statistik, namely data on inflation, foreign investment, domestic investment, corporate income tax (PPh) rates and per capita income. The analytical method used in this research uses multiple linear regression. The research results show that the independent variables of foreign investment and domestic investment have a significant effect on Indonesia's gross domestic product per capita, while the independent variables of inflation and corporate income tax rates do not have a significant effect on Indonesia's gross domestic product per capita. Simultaneously, the independent variables inflation, foreign investment, domestic investment and corporate income tax rates have a significant effect on Indonesia's gross domestic product per capita